1991
DOI: 10.1159/000125909
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between the Noradrenergic and Opioid Peptidergic Systems in Controlling the Electrical Activity of Luteinizing Hormone-Releasing Hormone Pulse Generator in Ovariectomized Rats

Abstract: The effects of noradrenergic and opioid peptidergic receptor blockade, either alone or in combination, on the electrical activity of luteinizing hormone-releasing hormone (LHRH) pulse generator were studied in ovariectomized rats fitted with chronically implanted electrode arrays in the medial basal hypothalamus. Both α- and β-adrenergic receptor antagonists, i.e. phenoxybenzamine (5 mg/kg i.v.) and propranolol (5 mg/kg i.v.), respectively, significantly increased the intervals between characteristic increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 29 publications
3
30
0
Order By: Relevance
“…It has been demonstrated that electrophysiological manifestations of the GnRH pulse generator are represented as characteristic increases in MUA (MUA volleys) that are exclusively associated with LH pulses in the monkey [8], rat [9] and goat [10,11]. It might be that observed MUA volleys reflect the pulsatile activation of GnRH nerve terminals as they traverse en passant to the ME.…”
mentioning
confidence: 99%
“…It has been demonstrated that electrophysiological manifestations of the GnRH pulse generator are represented as characteristic increases in MUA (MUA volleys) that are exclusively associated with LH pulses in the monkey [8], rat [9] and goat [10,11]. It might be that observed MUA volleys reflect the pulsatile activation of GnRH nerve terminals as they traverse en passant to the ME.…”
mentioning
confidence: 99%
“…Because SP did not modify GnRH release in animals with altered plasma gonadal steroids levels, we infer that gonadal steroids play an important role in the action of SP on GnRH release into the pituitary portal blood. One of the possible mechanisms explaining this steroid influence of SP action on hypothalamic GnRH neurons is that SP exerts its effect through the other inhibitory and/or stimulatory neurons controlling GnRH release into pituitary portal blood whose activity closely depends on the levels of circulating gonadal steroids [50, 51, 52, 53, 54, 55, 56]. …”
Section: Discussionmentioning
confidence: 99%
“…The invariable association between these MUA volleys and the initiation of LH pulses (Fig. 1) observed under a variety of experimental circumstances in the rhesus monkey (5-12), rat (13)(14)(15)(16)(17)(18), and…”
mentioning
confidence: 91%